Analisis Perbedaan Penjualan, Harga dan Struktur Pasar Ternak Sapi Kurban Periode Sebelum, Awal dan Masa Pandemi Covid-19 di Kabupaten Batang - Firmansyah Firmansyah; Muhammad Hafidz Fajri; Wahyu Akbar; Fachroerrozi Hoesni; Afriani H; Farizal Farizal (Ekonomis: Journal of Economics and Business, 2023)
This study aims to determine the differences in the number and price of sacrificial cattle sold before the pandemic and during the Covid-19 Pandemic and to analyze the market structure for sacrificial cattle in Batang Hari Regency based on the concentration of sellers. This study used a survey method by taking 50% of the total sub-districts in Batang Hari Regency. Then the data was obtained from a sample of sacrificial cattle traders who were taken by the census in the selected sub-districts. In this study seen from the concentration of sellers using the concentration ratio formula (Kr) and market share (market share). Data were analyzed using the data distribution normality test with the Kolmogorov-Smirnov test and the Shapiro-Wilk test. Test the difference using the Non-Parametric Test using the Kruskal Wallis Test followed by the Post Hoc Test using the Mann-Whitney Test. In conclusion, there was a difference in the number of sacrificial cattle sold by sacrificial cattle traders in Batang Hari District before the pandemic and during the Covid-19 Pandemic. There was a difference in the selling price of sacrificial cattle by cattle traders in Batang Hari District before the pandemic and during the Pandemic. Covid-19. The structure of the market for sacrificial cattle in Batang Hari Regency, based on the concentration of sellers, is an oligopoly of moderate concentration